2012
DOI: 10.1029/2012je004223
|View full text |Cite
|
Sign up to set email alerts
|

Angular momentum budget in General Circulation Models of superrotating atmospheres: A critical diagnostic

Abstract: 1] To help understand the large disparity in the results of circulation modeling for the atmospheres of Titan and Venus, where the whole atmosphere rotates faster than the surface (superrotation), the atmospheric angular momentum budget is detailed for two General Circulation Models (GCMs). The LMD GCM is tested for both Venus (with simplified and with more realistic physical forcings) and Titan (realistic physical forcings).The Community Atmosphere Model is tested for both Earth and Venus with simplified phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 33 publications
4
43
0
Order By: Relevance
“…Given our inability to reproduce these winds, it is our conclusion that the CAM 3 model running the finite volume dynamical core in its current form is incapable of reproducing Titan's superrotating winds. This conclusion is supported by the angular momentum analysis of Lebonnois et al (2012b), who compared the angular momentum terms of several GCMs on a modified Earth, Venus, and Titan. They found that the CAM finite volume dynamical core has errors in its angular momentum conservation that affect its ability to reproduce superrotation.…”
Section: Ad Hoc Forcing and Dynamicssupporting
confidence: 51%
See 1 more Smart Citation
“…Given our inability to reproduce these winds, it is our conclusion that the CAM 3 model running the finite volume dynamical core in its current form is incapable of reproducing Titan's superrotating winds. This conclusion is supported by the angular momentum analysis of Lebonnois et al (2012b), who compared the angular momentum terms of several GCMs on a modified Earth, Venus, and Titan. They found that the CAM finite volume dynamical core has errors in its angular momentum conservation that affect its ability to reproduce superrotation.…”
Section: Ad Hoc Forcing and Dynamicssupporting
confidence: 51%
“…It reaches equilibrium near a tropospheric superrotation index of 2. It is clear our non-forced model does not exhibit the superrotation in Titan's atmosphere that other Titan GCMs have recently been able to achieve (Newman et al, 2011;Lebonnois et al, 2012b). Other GCMs indicate that Titan's atmosphere may take dozens of Titan years to spin up.…”
Section: Ad Hoc Forcing and Dynamicsmentioning
confidence: 73%
“…Note that some past studies have found that the CAM finite volume dynamical core failed to capture the upper atmosphere superrotating winds of Titan and Venus (Parish et al 2011;Lebonnois et al 2012;Larson et al 2014). However, here we find no resultant differences in surface climate for slow rotating Earth-like planets using all three dynamical cores available in CAM.…”
Section: Control Simulationsmentioning
confidence: 99%
“…For planetary applications, it will be important to also check the discrete angular momentum budget (Lebonnois et al, 2012;Lauritzen et al, 2014a).…”
Section: Outlook For Dynamicomentioning
confidence: 99%